Acid-hybridized expanded perlite as a composite phase-change material in wallboards. Issue 81 (3rd September 2015) - Peng, Kang; Zhang, Jinyi; Yang, Huaming; Ouyang, Jing
<x xml:space="preserve">Abstract</x> Form-stable composite phase change materials (PCMs) for use in wallboards were prepared by absorbing stearic acid (SA) and lauric acid (LA) eutectic mixtures into the pores of expanded perlite (EP) via vacuum impregnation.